Carbon sequestration with reforestations and biodiversity-scenic values - Caparros, A.; Cerdá, E.; Ovando, P.; Campos, P. (Environmental and Resource Economics, 2010)
This paper presents an optimal control model to analyze reforestations with two different species, including commercial values, carbon sequestration and biodiversity or scenic values. We solve the model qualitatively with general functions and discuss the implications of partial or total internalization of environmental values, showing that internalizing only carbon sequestration may have negative impacts on biodiversityscenic values. To evaluate the practical relevance, we compare reforestations in the South-west of Spain with cork-oaks (a slow growing native species) and with eucalyptus (a fast growing alien species). We do the analysis with two different carbon crediting methods: the Carbon Flow Method and the Ton Year Accounting Method. With the .first method forest surface increases more, but using mainly eucalyptus. With the second, additional reforestations are done mainly using cork-oaks. We value the impact on visitors of these reforestations using stated preferences methods, showing that when these values are internalized cork-oaks are favored.
Keywords: Biodiversity; Carbon Accounting; Carbon Sequestration; Forests; Optimal Control; Scenic; Stated Preferences

Towards the dehesa total income accounting: theory and operative Monfragüe study cases - Campos, P.; Rodriguez, Y.; Caparros, A. (Investigación Agraria: Sistemas y Recursos Forestales, 2001)
There has been, from the beginning of the 1970s, a controversial debate on the income measurement of natural resource exploitation and sustainability both commercial and environmental of their economic resources. Treeless pastures and woodlands have been the focus of less research than has timber forestland. Up to today, institutional timber forestland accounting proposals have not integrated non-excludable and other non-market benefits into total income measurement of forestland. This paper shows a complete accounting system that can incorporate any economic benefit and cost that could accrue from active and passive uses of forestland, whether or not the economic effects are the result of on-site and off-site land uses. An application to the Spanish dehesas at Monfragüe area gives a tentative total income measurement under this new accounting proposal. The dehesa woodland study represents one of the most complex forestland uses system.
Keywords: Commercial income; Dehesa; Environmental income; Forestland accounting; Total income